Learning Strategies For Writing Skills With Self-Efficacy Based/ استراتيجيات تعليم مهارة الكتابة بضوء الكفاءة الذاتية - Ade Destri Deviana; Lailatul Qomariyah; Faisal Mubarak; Akhmad Sauqi Ahya (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
In writing skill learning at university, students can organize information, thoughts, and feelings in the Arabic language according to grammar by understanding concepts, writing processes, and developing paragraphs for essays. For this, lecturers can challenge their students to be confident that they can do assigned tasks well, develop new writings and innovations to them the writing, and produce achievements, and the teacher expected learning strategies. The study aims to describe the learning strategies used self-efficacy-based in writing skill learning. The study used direct observation in the field and the researcher as a moderate participant with a descriptive qualitative approach to 65 students of the fifth level of the Arabic Language Education Department, the state College of Quranic Science Amuntai Indonesia. The results are there were six strategies according to self-efficacy-based in writing skill learning, namely: Direct interaction meeting, simulation, and modeling, independent study, framework and feedback, relaxation, then suggestopedia.